2014
DOI: 10.2337/db14-0979
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Cyclooxygenase-2 Expression Protects Against Diet-Induced Steatosis, Obesity, and Insulin Resistance

Abstract: Accumulation evidence links obesity-induced inflammation as an important contributor to the development of insulin resistance, which plays a key role in the pathophysiology of obesity-related diseases such as type 2 diabetes and nonalcoholic fatty liver disease. Cyclooxygenase (COX)-1 and -2 catalyze the first step in prostanoid biosynthesis. Because adult hepatocytes fail to induce COX-2 expression regardless of the proinflammatory stimuli used, we have evaluated whether this lack of expression under mild pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 33 publications
5
42
0
1
Order By: Relevance
“…These results agree with the data reported in our study (3) in which decreased expression of proinflammatory cytokines in white fat revealed protection against low-grade chronic inflammation. In addition, COX-2-dependent prostaglandin E 2 , acting via EP2/EP4 Gbg dimers, enhanced insulin signaling through Akt phosphorylation.…”
supporting
confidence: 93%
“…These results agree with the data reported in our study (3) in which decreased expression of proinflammatory cytokines in white fat revealed protection against low-grade chronic inflammation. In addition, COX-2-dependent prostaglandin E 2 , acting via EP2/EP4 Gbg dimers, enhanced insulin signaling through Akt phosphorylation.…”
supporting
confidence: 93%
“…Analysis of pathways and networks using the DAVID platform identified several candidate pathways for these miRNA target genes. Among them, the insulin signaling pathway was of interest because, in accordance with our previous results, COX-2 is implicated in protection against hepatic insulin resistance in mice on a high-fat diet (14). Only eight of these miRNAs (miR-146b, Let-7b, miR-183, miR-181a1*, miR-23b, miR-184, miR-204, and Let-7a) have target genes involved in the insulin signaling pathway, and their data were confirmed by real-time RT-PCR in liver extracts from Wt and COX-2-Tg mice.…”
Section: Resultssupporting
confidence: 64%
“…We analyzed the enriched signaling pathways among the predicted gene targets of the miRNAs regulated by COX-2 and focused on the insulin signaling pathway based on our previous results that indicated that COX-2 reduces liver damage induced by hyperglycemia (15) and protects against adiposity, inflammation, and hepatic insulin resistance in mice challenged with a high-fat diet (14). These miRNA target genes were validated by real-time RT-PCR and presented increased expression in COX-2-Tg liver and in both CHL and NCL cells expressing COX-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is determined by the number and volume of adipocytes in adipose tissue, which not only depends on intracellular triglyceride synthesis and catabolic effi ciency, but also on the balance between cell proliferation and death, including necrosis and apoptosis (30)(31)(32)(33)(34). Cell proliferation is the result of mitosis that is regulated by the cell cycle and requires a variety of regulatory mechanisms to genes, either positively or negatively, to coordinate each other (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%